Neospora caninum and BDV prevalence in a farm with reproductive problems in Sopó (Cundinamarca) - García-Chaparro, John Fredy; Moreno-Figueredo, Giovanni; Cruz-Carrillo, Anastasia Catalina (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The research objective was to determine the Neospora caninum and the bovine viral diarrhea virus prevalence in a cattle farm, with reproductive problems in the Bogotá Sabana region, and their relation to the abortions incidence. Blood serum samples were taken from 397 high milk production animals, with randomly selected reproductive history. These animals were located in the Sopó muncipality (Cundinamarca Departament). The indirect immunofluorescence was used for N. caninum and the serum neutralization for BVD. The procedures were performed in the Infectious Diseases Laboratory at the Parma University (Italy).  The study showed a 10.37% prevalence for BVD and 21.26% for N. caninum. Statistically there was no relationship with respect to reproductive problems. According to the results obtained, there was a more significant presence of N. caninum in relation to BVD, in the dairy herd under study.